Computerized Adaptive Testing in Reading Comprehension - Lim Tock Keng, Ho Wah Kam (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract: A Computerized Adaptive Testing (CAT) project in reading comprehension was established to develop multiple choice tests across four grade levels, Primary 3 and 5, and Secondary I and 3. CAT is interactive and allows participants to select their own entry points to the test and gives feedback on their performance. Building a CAT system required the development of an item bank, selection of item and items order to be presented in a test, and evaluating the test for difficulty. The creation of the item bank involved the specifying reading comprehension skills, writing items, field testing, item analysis and calibration. The software, MICROCAT, was used to develop an item bank, to select items and item order to be presented in a test, and to evaluate the test for difficulty. The project is currently at the stage of field testing.